Porous Metals and Metallic Foams: Current Status and Recent Developments - Lefebvre, L.-P.; Banhart, J.; Dunand, D. C. (Advanced engineering materials, 2008)
Porous metals and metallic foams are presently the focus of very active research and development activities. There are currently around 150 institutions working on metallic foams worldwide, most of them focussing on their manufacture and characterisation. Various companies are developing and producing these materials which are now being used in numerous industrial applications such as lightweight structures, biomedical implants, filters, electrodes, catalysts, and heat exchangers. This review summarizes recent developments on these materials, with particular emphasis on research presented at the latest International Conference on Porous Metals and Metallic Foams (MetFoam 2007). Porous metals and metallic foams are presently the focus of very active research and development activities. There are currently around 150 institutions working on metallic foams worldwide, most of them focussing on their manufacture and characterisation. Various companies are developing and producing these materials which are now being used in numerous industrial applications such as lightweight structures, biomedical implants, filters, electrodes, catalysts, and heat exchangers. This review summarizes recent developments on these materials, with particular emphasis on research presented at the latest International Conference on Porous Metals and Metallic Foams (MetFoam 2007).